PERAN OTORITAS JASA KEUANGAN DALAM PENGAWASAN PAY LATER PADA APLIKASI SHOPEE - Shella Bunga Slamet Lantini; Rafli Akmal Maulana; Arina Bunganingtyas; Melisa Arinda Putri; Endang Kartini (Melati Institute, 2023)
The Financial Services Authority (OJK) plays an important role in overseeing the Pay Later feature in the Shopee app. This feature allows users to purchase products on credit and pay the installments within a certain period of time. OJK ensures that the use of this feature is done fairly and transparently. Pay Later is one of the features offered by e-commerce applications such as Shopee as an alternative payment for consumers. Although it has significant benefits for consumers, the use of Pay Later also carries risks related to personal financial management and can have an impact on financial system stability. Therefore, the role of the Financial Services Authority (OJK) in overseeing the use of Pay Later on the Shopee application is very important. This article also discusses OJK's role in emphasizing supervision of consumers so that they can use the Pay Later feature wisely. That way, the Pay Later feature can provide positive benefits for all parties involved.